Anatomy of Sarcotheca celebica’s vegetative organs growing in Morowali on Ultramafic and Limestone Soils - Harso, Wahyu; Rasyiid, Mustafid; Ramadanil, Ramadanil; Umrah, Umrah; Iqbal, Moh. (Jurnal Biologi Tropis, 2025)
Sarcotheca celebica is an endemic Sulawesi plant capable of growing in ultramafic and calcareous soils. The anatomical structure of its vegetative organs plays a role in adaptation to extreme environments. This study aimed to compare the anatomy of leaves, stems and roots of S. celebica in both soil types. Microscopic preparations of leaves, stems and roots were made with the Free Hand Section method, documented using Optilab Viewer 2.2, and measured with Image Raster 3. Statistical analysis was conducted with the T-test. The results showed anatomical variations in response to soil conditions. S. celebica plants in calcareous soil had longer and wider stomata, but with lower density than those in ultramafic soils. In addition, leaf and cuticle thickness were higher in S. celebica plants on calcareous soils. However, the peridemis/floem ratio in stems and peridermis/endodermis in roots did not show significant differences. Overall, S. celebica leaves were more responsive to soil differences than stems and roots. This study is important for understanding the mechanisms of plant adaptation to extreme soil conditions and the implications for the sustainability of the species in its natural habitat.